2018
DOI: 10.1093/nar/gky886
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of a G-quadruplex formed by four d(G4C2) repeats: insights into structural polymorphism

Abstract: Most frequent genetic cause of amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), is a largely increased number of d(G4C2)n•(G2C4)n repeats located in the non-coding region of C9orf72 gene. Non-canonical structures, including G-quadruplexes, formed within expanded repeats have been proposed to drive repeat expansion and pathogenesis of ALS and FTD. Oligonucleotide d[(G4C2)3G4], which represents the shortest oligonucleotide model of d(G4C2) repeats with the ability to form a unimolecular G-q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 69 publications
2
30
0
Order By: Relevance
“…Given these favourable results, we turned to a different target type, the r(G 4 C 2 ) repeat expansion [r(G 4 C 2 ) exp ] found in the C9orf72 gene, the most common genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia (c9ALS/FTD) 33 , 34 . This RNA folds into two structures that are in equilibrium in vitro, a G-quadruplex 35 and hairpin displaying a periodic array of 1 × 1 G/G internal loops in its stem 36 , 37 . The hairpin structure causes toxicity by an RNA gain-of-function mechanism, in particular undergoing repeat-associated non-ATG (RAN) translation 37 to form toxic dipeptide repeats that cause neuronal death ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given these favourable results, we turned to a different target type, the r(G 4 C 2 ) repeat expansion [r(G 4 C 2 ) exp ] found in the C9orf72 gene, the most common genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia (c9ALS/FTD) 33 , 34 . This RNA folds into two structures that are in equilibrium in vitro, a G-quadruplex 35 and hairpin displaying a periodic array of 1 × 1 G/G internal loops in its stem 36 , 37 . The hairpin structure causes toxicity by an RNA gain-of-function mechanism, in particular undergoing repeat-associated non-ATG (RAN) translation 37 to form toxic dipeptide repeats that cause neuronal death ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the directionality of hydrogen bonds within a G-quartet, DNA G-quadruplexes display a remarkable variety of folding topologies ( 5 , 6 ). In spite of the ever growing number of high-resolution structures, prediction or design of a particular G4 fold is challenging, as a variety of factors such as buffer pH ( 7 , 8 ) or the nature of coordinating cations ( 9 , 10 ) may critically influence G4 folding in addition to a heavy dependence on primary sequence ( 11 , 12 ). In this respect, the glycosidic torsion angle determining the relative orientation of base and sugar moieties is of particular importance, as a switch in G-tract orientation or tetrad polarity is always accompanied by a syn–anti or anti–syn transition (Figure 1A ).…”
Section: Introductionmentioning
confidence: 99%
“…The G-quartets further stack to produce a G-quadruplex structure, generally stabilized by metal cations, e.g., K + , Na + , Ba 2+ , or Sr 2+ , inside the core, though exceptions have been reported 53,54 . However, exceptions to this traditional structural pattern have been observed in many natural/synthetic G-quadruplexes 39,[55][56][57][58] . For example, Krauss et al reported the crystal structure of a thrombin-bound DNA aptamer, in which the orientation of guanine bases broke the Hoogsteen hydrogen-bonded cyclic pattern, but a G-quartet structure was still produced 55 .…”
Section: Resultsmentioning
confidence: 96%